An Investigation into First-year Students’ Autonomous Learning in Class and Outside Classrooms at the English for Specific Purposes Department, Hanoi University - Ngo Thi Thu Trang; Ta Thi Thanh Hien; Kieu Thi Thu (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
For a smooth transition from high school setting to university environment students who are enrolled in the English for Specific Purposes Department (ESPD), Hanoi University need to practice essential study skills. Since English is used as a medium of instruction to non-English majors, many freshmen have been struggling in despair. In response to students’ needs the ESPD have introduced different components to help students build effective study habits. In their first term students undergo a 10-week course called Learners Training which is designed to empower students in taking charge of their studies. To evaluate the implication and effectiveness of the named course the writers of this paper conducted research in order to explore students’ practice of self-study within and beyond the classroom context. This paper attempted to examine students’ awareness, their practice and teachers’ role in the whole process of developing learners’ autonomy. The author group employed survey questionnaires to probe into the research issues. The findings indicated that students were cognizant of the benefits of autonomous learning and their English learning activities exhibited richness and diversity. However, there was still room for improvement in students’ demonstration of self-directed learning activities in class. These findings will hopefully provide lecturers with a precise understanding of students’ autonomous learning. This understanding, in turn, can aid in fostering autonomous learning among students through tailored and recommended teaching activities. Received 5th September 2023; Revised 20th September 2023; Accepted 5th October 2023